Complex Interactions Between Membrane-Bound Organelles, Biomolecular Condensates and the Cytoskeleton - Koppers, Max; Özkan, Nazmiye; Farías, Ginny G. (Frontiers in Cell and Developmental Biology, 2020)
Membrane-bound and membraneless organelles/biomolecular condensates ensure compartmentalization into functionally distinct units enabling proper organization of cellular processes. Membrane-bound organelles form dynamic contacts with each other to enable the exchange of molecules and to regulate organelle division and positioning in coordination with the cytoskeleton. Crosstalk between the cytoskeleton and dynamic membrane-bound organelles has more recently also been found to regulate cytoskeletal organization. Interestingly, recent work has revealed that, in addition, the cytoskeleton and membrane-bound organelles interact with cytoplasmic biomolecular condensates. The extent and relevance of these complex interactions are just beginning to emerge but may be important for cytoskeletal organization and organelle transport and remodeling. In this review, we highlight these emerging functions and emphasize the complex interplay of the cytoskeleton with these organelles. The crosstalk between membrane-bound organelles, biomolecular condensates and the cytoskeleton in highly polarized cells such as neurons could play essential roles in neuronal development, function and maintenance.